2020
DOI: 10.3389/fcell.2020.00414
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of FAM46A, a Non-canonical Poly(A) Polymerase, Promotes Hemin-Induced Hemoglobinization in K562 Cells

Abstract: FAM46A belongs to the FAM46 subfamily of the nucleotidyltransferase-fold superfamily and is predicted to be a non-canonical poly(A) polymerase. FAM46A has been linked to several human disorders including retinitis pigmentosa, bone abnormality, cancer, and obesity. However, its molecular and functional characteristics are largely unknown. We herein report that FAM46A is expressed in cells of the hematopoietic system and plays a role in hemin-induced hemoglobinization. FAM46A is a nucleocytoplasmic shuttle prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“… 47 , 48 In addition, Tent5a was expressed in hematopoietic system cells and played an important role in heme‐induced hemoglobinization. 49 Deletion of the Tent5a gene led to abnormal formation of eye and body color in Xenopus. 50 In this study, we first reported the function of Tent5a in myoblasts and myogenic differentiation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 In addition, Tent5a was expressed in hematopoietic system cells and played an important role in heme‐induced hemoglobinization. 49 Deletion of the Tent5a gene led to abnormal formation of eye and body color in Xenopus. 50 In this study, we first reported the function of Tent5a in myoblasts and myogenic differentiation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%